Metallic lithium-high-entropy solid electrolyte interphase film composite negative electrode material and preparation method

CN122992022APending Publication Date: 2026-10-27ZHEJIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611095713.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]然而,现有人工SEI技术存在明显不足:(1)组分单一,性能权衡受限:常规的人工SEI多为单一组分含锂化合物,如LiF、Li2O、Li3N、Li2CO3等

Benefits of technology

[0025]1、本发明的复合结构中,高熵SEI膜的室温离子电导率可达到5×10-6至2×10-5S/cm,相比纯LiF膜(约10-9S/cm)提高了3至4个数量级。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992022A_ABST
    Figure CN122992022A_ABST
Patent Text Reader

Abstract

The application relates to a new material preparation technology, and aims to provide a metal lithium-high-entropy solid electrolyte interface film composite negative electrode material and a preparation method. ‑ 2‑ 3‑ ‑ 2‑ ‑ ‑ The seven kinds of anions are single-phase amorphous lithium-containing inorganic compound thin films. The application utilizes the random and uniform distribution of the seven kinds of anions with different sizes and different charge densities in the amorphous network to form a unique composite structure with long-range disorder and short-range multi-component coordination; the room temperature ionic conductivity is significantly improved compared with a pure LiF film; the stable cycle time and critical current density are significantly better than those of a single-component SEI film; by constructing a multi-scale lithium ion migration channel network, the grain boundaries are completely eliminated, and the multi-component synergistic toughening effect effectively inhibits lithium dendrite growth; the application can break through the limitations of ionic conductivity, mechanical stability and component regulation precision at the same time.​​​​​​
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of new material preparation technology, specifically to a lithium metal-high entropy solid electrolyte interface film composite anode material and its preparation method. Background Technology

[0002] Lithium metal possesses an extremely high theoretical specific capacity (3860 mAh / g) and the lowest electrochemical potential (-3.04V vs. standard hydrogen electrode), making it an ideal anode material for next-generation high-energy-density batteries. However, lithium metal anodes face two major challenges in practical applications: first, continuous side reactions occur at the interface between lithium metal and the electrolyte (whether liquid or solid), consuming active lithium and electrolyte, leading to low coulombic efficiency; second, uneven nucleation and growth during lithium deposition / desorption can induce lithium dendrites, piercing the separator or electrolyte layer, causing internal short circuits or even thermal runaway. To address these issues, constructing an artificial solid electrolyte interphase (SEI) membrane is a recognized effective strategy. By pre-growing a functional protective film on the surface of lithium metal, electron transport can be isolated, preventing direct contact between the electrolyte and lithium metal, while simultaneously providing a transport channel for lithium ions.

[0003] However, existing artificial SEI technologies have significant shortcomings: (1) Single component, limited performance trade-offs: Conventional artificial SEIs are mostly single-component lithium compounds, such as LiF, Li2O, Li3N, Li2CO3, etc. These materials have inherent contradictions in performance. For example, LiF has good electronic insulation and high shear modulus, but its ionic conductivity is extremely low (only ~10). -9 The S / cm ratio will greatly increase the interfacial impedance of the battery; Li3N has a very high ionic conductivity (~10 S / cm), which will greatly increase the interfacial impedance of the battery; -3 (2) Long-range ordered structure, which easily induces dendrite penetration: Crystalline single-component SEI has a large number of grain boundaries and defects. These grain boundaries are mechanically weak points and fast channels for lithium ion transport, which will induce lithium to be preferentially deposited at the grain boundaries. The resulting local stress concentration will eventually lead to the SEI film cracking along the grain boundaries, providing a path for lithium dendrite penetration. (3) Low precision of preparation method, unable to perform precise control of multiple components: Traditional artificial SEI preparation methods such as immersion method and scraping method are difficult to precisely control the composition, thickness and uniformity of the film at the nanoscale, and cannot achieve atomic-level uniform mixing and quantitative control of multiple components.

[0004] Therefore, there is an urgent need for a novel SEI design concept and a controllable preparation method that can enable the interfacial membrane to simultaneously overcome the limitations of ionic conductivity, mechanical stability, and component control precision. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a lithium metal-high entropy solid electrolyte interface film composite anode material and its preparation method.

[0006] To solve the technical problem, the solution of the present invention is:

[0007] A lithium metal-high-entropy solid electrolyte interfacial membrane composite anode material is provided, comprising a lithium metal substrate and a high-entropy solid electrolyte interfacial membrane (high-entropy SEI membrane) grown in situ on the surface of the substrate, the latter containing F - O 2- N 3- Cl - S 2- ,Br - I - These are single-phase amorphous lithium-containing inorganic compound films containing seven anions.

[0008] As a preferred embodiment of the present invention, in the high-entropy solid electrolyte interface membrane, the molar fraction of lithium ions in the high-entropy SEI membrane is 55%~70%, and the remaining molar percentage is composed of the seven anions.

[0009] In a preferred embodiment of the present invention, the total amount of the seven anions is 100 mol%, and the mole fraction of each anion is: F - 20%–40%, O 2- 10%–25%, N 3- 10%–25%, Cl - 5%–15%, S 2- 5%–15%, Br - 3% to 10%, I - It ranges from 3% to 10%.

[0010] As a preferred embodiment of the present invention, the thickness of the high-entropy solid electrolyte interface film is 70~480 nanometers.

[0011] This invention also provides a method for preparing the aforementioned lithium metal-high entropy solid electrolyte interface film composite anode material, comprising the following steps:

[0012] (1) The lithium metal used as the negative electrode substrate is shaped and cleaned;

[0013] (2) In an inductively coupled plasma enhanced chemical vapor deposition system, a precursor gas containing different anions is introduced simultaneously; a single-phase amorphous lithium-containing inorganic compound film containing seven anions is deposited in situ on the surface of a lithium metal substrate by plasma in situ deposition.

[0014] (3) After heating and heat preservation treatment of the material deposited on the surface, it is annealed in situ by natural cooling to obtain the metal lithium-high entropy solid electrolyte interface film composite negative electrode material.

[0015] As a preferred embodiment of the present invention, the shaping in step (1) refers to cutting and flattening the lithium metal foil in an inert atmosphere or vacuum environment; the cleaning process refers to placing the lithium metal foil in a deposition chamber, evacuating it, and then introducing argon gas to bombard and clean its surface with radio frequency plasma to remove the natural oxide layer and adsorbed impurities on the surface.

[0016] As a preferred embodiment of the present invention, the precursor gas in step (2) refers to a precursor gas containing different anions; wherein, the fluorine source is CHF3, the oxygen source is high-purity O2, the nitrogen source is high-purity N2, the chlorine source is TiCl4 vapor, the sulfur source is SF6, the bromine source is BBr3 vapor, and the iodine source is HI gas; both TiCl4 vapor and BBr3 vapor are introduced into the deposition system by bubbling using argon as the carrier gas.

[0017] As a preferred embodiment of the present invention, in step (2), the flow rate of each gas, the total pressure of the chamber, the plasma radio frequency power and the deposition time are adjusted; wherein, each precursor gas is precisely controlled by an independent mass flow meter, and all gas pipelines are heated and kept at 40~60℃; the steady-state pressure of the deposition chamber is maintained at 5~30 Pa; the plasma radio frequency power supply frequency is 13.56 MHz and the power is 100~300 W; the deposition time is 5~60 minutes.

[0018] As a preferred embodiment of the present invention, in step (2), the temperature of the sample stage supporting the lithium metal substrate is controlled by a circulating constant temperature water cooling system during the deposition process, and the temperature is maintained at 20~35℃.

[0019] As a preferred embodiment of the present invention, in step (3), after deposition, the sample stage is heated to 40~80°C using the heating resistance wire built in it, kept at that temperature for 5~30 minutes and then naturally cooled to below 30°C. The residual stress in the film is released and the amorphous structure is stabilized by in-situ annealing.

[0020] Description of the invention principle:

[0021] The high-entropy solid electrolyte interface membrane (hereinafter referred to as high-entropy SEI membrane) is formed on the substrate surface by in-situ growth in the lithium metal-high-entropy solid electrolyte interface membrane composite anode material proposed in this invention. Its core innovation is to utilize the random and uniform distribution of seven anions of different sizes and charge densities in the amorphous network to form a unique structure with long-range disorder and short-range multi-component coordination.

[0022] 1. In terms of improving ionic conductivity: In single-component amorphous SEIs (such as pure LiF), Li + The migration of these anions requires overcoming the potential barrier formed by a single anion. When seven anions coexist, the ionic radii of each anion increase from Fi... - (133 pm), O 2- (140pm), N 3- (146 pm), S 2- (184 pm), Cl - (181 pm), Br - (196 pm) to I - (220 pm) exhibits a gradient distribution, thus forming a multi-scale, widely distributed lithium-ion channel network. The smaller F... - O 2- N 3- Construct a dense channel framework with medium-sized S-shaped channels. 2- and Cl - Widen the channel diameter, the largest Br - and I - This results in larger channel windows locally. The synergistic effect of this multi-scale channel significantly reduces the ion migration activation energy from 0.85 eV in pure LiF to 0.25~0.40 eV, and increases the ionic conductivity by 3~4 orders of magnitude compared to pure LiF films.

[0023] 2. In suppressing lithium dendrites: The amorphous nature of the seven-element high-entropy SEI film eliminates grain boundaries, a weak path for preferential dendrite penetration. Simultaneously, the significant size differences among the seven anions (maximum difference of 87 pm, approximately 65% ​​relative difference) lead to highly fluctuating local stress fields at the nanoscale. When local stress is applied to the tip of a lithium dendrite, this stress cannot be concentrated and released along a single plane, but is instead widely dispersed and dissipated at the nanoscale, preventing crack initiation and propagation, thus giving the film excellent puncture resistance.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. In the composite structure of this invention, the room temperature ionic conductivity of the high-entropy SEI film can reach 5 × 10⁻⁶. -6 Up to 2×10 -5 S / cm, compared to pure LiF membrane (approximately 10 S / cm), -9 The S / cm ratio increased by 3 to 4 orders of magnitude.

[0026] 2. In symmetric lithium battery testing, this composite structure can stably cycle for more than 1000 hours at a current density of 1 mA / cm² and a deposition capacity of 1 mAh / cm², with a critical current density exceeding 3 mA / cm², which is significantly better than single-component SEI films.

[0027] 3. This invention utilizes the gradient size distribution of seven anions to construct a multi-scale lithium-ion migration channel network, while completely eliminating grain boundaries. The synergistic toughening effect of the multi-components effectively suppresses lithium dendrite growth.

[0028] 4. The preparation method of the present invention is based on seven-path precursor plasma co-deposition, and the gas flow rate of each path is independently adjustable, which can precisely control the composition and ratio of the seven anions in the membrane and has good reproducibility. Attached Figure Description

[0029] Figure 1 This is a cross-sectional SEM image of the high-entropy SEI membrane in Embodiment 1 of the present invention.

[0030] Figure 2 This is the X-ray diffraction (XRD) pattern of the high-entropy SEI film in Example 1 of the present invention.

[0031] Figure 3 This is a cross-sectional SEM image of the high-entropy SEI membrane in Embodiment 2 of the present invention.

[0032] Figure 4 This is the X-ray diffraction (XRD) pattern of the high-entropy SEI film in Example 2 of the present invention. Detailed Implementation

[0033] Part 1 Overview of the Invention Scheme

[0034] 1. Lithium metal-high entropy solid electrolyte interface film composite anode material

[0035] (1) The negative electrode material includes a lithium metal substrate and a high-entropy solid electrolyte interphase (SEI) film grown in situ on the surface of the substrate. The latter contains F - O 2- N 3- Cl - S 2- ,Br - I - These are single-phase amorphous lithium-containing inorganic compound films containing seven anions.

[0036] The thickness of high-entropy SEI films ranges from 50 to 500 nanometers. When the thickness is less than 50 nanometers, the film layer does not cover the metallic lithium sufficiently and has defects such as pinholes; when the thickness is greater than 500 nanometers, the lithium-ion transport path is too long and the interface impedance increases.

[0037] (2) In this high-entropy SEI membrane, the molar fraction of lithium ions is 55%~70%, and the remaining molar percentage is composed of the seven anions. The total amount of the seven anions is 100 mol%, and the molar fraction of each anion is: F - 20%–40%, O2- 10%–25%, N 3- 10%–25%, Cl - 5%–15%, S 2- 5%–15%, Br - 3% to 10%, I - It ranges from 3% to 10%.

[0038] F - It is a fundamental component that ensures the electronic insulation and chemical stability of the film. When its content is below 20%, the film cannot effectively isolate the side reactions between metallic lithium and the external environment; when it is above 40%, the high entropy effect weakens, and the ionic conductivity drops to 10. -7 Below S / cm.

[0039] O 2- and N 3- It is a core component for constructing the amorphous network framework. 2- When the content is below 10%, the film density decreases; when it is above 25%, the film brittleness increases, and it is prone to cracking during cycling. 3- When the content is below 10%, it does not contribute enough to the ionic conductivity; when it is above 25%, the chemical stability of the film for metallic lithium deteriorates.

[0040] Cl - S 2- ,Br - I - Components for widening the channel. - and S² - The content of each component is controlled between 5% and 15%. Below 5%, the channel broadening effect is not obvious, while above 15%, it will cause excessive local structural distortion and destroy the characteristics of amorphous single phase. Br - and I - The two largest anions (Br) - Radius 196 pm, I - With a radius of 220 pm, a small amount can significantly broaden ion migration channels, but its size is similar to that of F. - When the difference (133 pm) is too large, and the content exceeds 10%, the amorphous structure will become unstable due to the excessive atomic size mismatch.

[0041] 2. Preparation method of lithium metal-high entropy solid electrolyte interface film composite anode material

[0042] (1) Pretreatment of lithium metal substrate:

[0043] The lithium metal used as the negative electrode substrate undergoes shaping and cleaning processes. Shaping refers to cutting and flattening the lithium metal foil in an inert atmosphere or vacuum environment. Cleaning involves placing the lithium metal foil in a deposition chamber, evacuating it, and then introducing argon gas to bombard its surface with radio frequency plasma to remove the natural oxide layer and adsorbed impurities.

[0044] A specific process example is: the base vacuum is better than 5×10. -4 Pa, argon flow rate 15~30 sccm, chamber pressure 8~15Pa, radio frequency power 40~80 W, cleaning time 3~10 minutes.

[0045] (2) Plasma in-situ deposition of high-entropy SEI films:

[0046] In an inductively coupled plasma enhanced chemical vapor deposition system, precursor gases containing different anions are introduced simultaneously; a single-phase amorphous lithium-containing inorganic compound film containing seven anions is deposited in situ on the surface of a lithium metal substrate by plasma in-situ deposition.

[0047] The precursor gases refer to precursor gases containing different anions; among them, the fluorine source is CHF3, the oxygen source is high-purity O2, the nitrogen source is high-purity N2, the chlorine source is TiCl4 vapor, the sulfur source is SF6, the bromine source is BBr3 vapor, and the iodine source is HI gas; both TiCl4 vapor and BBr3 vapor are introduced into the deposition system by bubbling using argon as the carrier gas.

[0048] During in-situ deposition, the flow rates of each gas, the total pressure of the chamber, the plasma radio frequency power, and the deposition time are adjusted, including: adjusting the anion content in the film by controlling the gas flow rate; adjusting particle transport, collision frequency, free path, and film density by controlling the total pressure of the chamber; adjusting activation ionization intensity, ion bombardment, reactivity, and film structure by controlling the plasma radio frequency power; and adjusting the film thickness by controlling the deposition time.

[0049] Specific examples are as follows: CHF3 flow rate is 4~12 sccm; high-purity O2 (purity ≥99.999%) flow rate is 1~4 sccm; high-purity N2 (purity ≥99.999%) flow rate is 2~7 sccm; TiCl4 vapor, using 2~6 sccm of argon as the carrier gas, is introduced into the deposition chamber at 20~30℃ via bubbling; SF6 flow rate is 2~6 sccm; BBr3 vapor, using 2~5 sccm of argon as the carrier gas, is introduced at 15~25℃ via bubbling; HI gas is introduced directly in gaseous form at a flow rate of 1~4 sccm. Each precursor gas is precisely controlled using an independent mass flow meter with a flow control accuracy of ±0.1 sccm. All gas pipelines are heated and insulated to 40~60℃ to prevent precursor vapors from condensing on the pipe walls. The steady-state pressure in the deposition chamber is maintained at 5–30 Pa, automatically adjusted by the opening of a throttle valve. The plasma RF power supply operates at the equipment's standard frequency (e.g., 13.56 MHz) with a power of 100–300 W, employing inductive coupling to excite the plasma. During deposition, a circulating constant-temperature water cooling system maintains the temperature of the lithium metal substrate on the sample stage at 20–35°C. The deposition time is 5–60 minutes.

[0050] (3) In-situ low-temperature annealing:

[0051] After deposition, all precursor gas sources and plasma power supplies were shut off to maintain a vacuum in the chamber. Then, using the heating resistance wire built into the sample stage, the deposited material was heated to 40–80°C. After holding at this temperature for 5–30 minutes, it was allowed to cool naturally to below 30°C. In-situ annealing was then performed to release residual stress within the film and stabilize the amorphous structure, ultimately yielding the lithium metal-high-entropy solid electrolyte interface film composite anode material.

[0052] Part Two: Specific Embodiments and Comparative Examples

[0053] In all embodiments and comparative examples, the testing methods for ionic conductivity and electrochemical performance are uniformly described as follows:

[0054] Ionic conductivity testing method: The ion-blocking electrode AC impedance method was used. The prepared lithium metal-high-entropy solid electrolyte interface film composite negative electrode material was cut into 15 mm diameter discs. In an argon-filled glove box, these discs were used as the middle layer, with a 15 mm diameter, 0.5 mm thick stainless steel (SS316L) disc on each side as ion-blocking electrodes, assembling an SS316L / high-entropy SEI / SS316L sandwich structure. This structure was then placed in a sealed coin cell casing and pressed under a constant pressure of 50 N. AC impedance testing was performed using an electrochemical workstation at a constant temperature of 25 ± 0.5 °C, with a test frequency range of 1 MHz to 0.1 Hz and an AC disturbance voltage amplitude of 10 mV. The resulting Nyquist plot showed a flattened semicircle in the high-frequency region and a straight line approximately perpendicular to the real axis in the low-frequency region. The high-frequency intercept of the high-frequency semicircle in the Nyquist plot was taken as the bulk resistance R. b (Ω), according to the formula σ = d / (R) b Calculate the ionic conductivity σ (S / cm) using the formula ×A), where d is the thickness of the high-entropy SEI film (obtained by cross-sectional SEM measurement, unit: cm), and A is the effective contact area between the stainless steel electrode and the SEI film (1.77 cm²). 2 ).

[0055] Symmetrical battery assembly and cycle testing method: Inside an argon-filled glove box, the prepared lithium metal-high-entropy solid electrolyte interphase (SEI) composite negative electrode material was cut into two 12 mm diameter discs. The two discs were stacked with their high-entropy SEI surfaces facing each other and placed into a sealed coin cell casing. They were then pressed together with a constant pressure of 30 N to assemble a lithium metal / high-entropy SEI / / high-entropy SEI / lithium metal symmetric battery. The assembled symmetric battery was placed in a constant temperature environment of 25 ± 0.5 °C and connected to a battery charge-discharge testing system for constant current charge-discharge cycle testing. The test procedure was as follows: A constant current density (1 mA / cm²) was applied... 2 The battery is charged (i.e., the lithium deposition process), and the charging cutoff condition is that the deposition capacity reaches a set value (1 mAh / cm³). 2 Then, discharge is performed at the same constant current density (i.e., lithium extraction process), with the discharge cutoff condition being that the cutoff voltage reaches a set value (e.g., 0.5 V). There is no rest time between each charge-discharge cycle, and the cycle continues until the battery short-circuits (manifested as a sudden drop in polarization voltage to below 10 mV and remaining thereafter) or the number of cycles reaches the set upper limit.

[0056] Critical current density test method: After the symmetrical cell assembly is completed, at 0.5 mA / cm²... 2 At the initial current density, five complete deposition / deposition cycles were performed at each current density (each deposition capacity was fixed at 1 mAh / cm³). 2), then at 0.5 mA / cm 2 The above process is repeated, gradually increasing the current density in increments. The polarization voltage at each current density is recorded. If, at a given current density, the polarization voltage fluctuates drastically or suddenly drops below 10 mV within five cycles, the battery is considered to have experienced a dendritic short circuit. The current density value of the previous stable cycle at that current density is the critical current density for that sample. Three symmetrical cells are tested in parallel for each sample, and the average value is taken.

[0057] Example 1

[0058] Preparation steps of composite anode materials:

[0059] (1) Pretreatment: In a glove box filled with argon and with water and oxygen levels below 0.1 ppm, a 50 μm thick lithium foil with a purity of 99.95% was flattened and placed on the sample stage of the ICP-PECVD chamber. The chamber was evacuated to a background vacuum of 4 × 10⁻⁶. -4 Pa. Introduce 15 sccm of high-purity argon gas, adjust the chamber pressure to 8 Pa, and turn on the radio frequency power supply to purge for 10 minutes at 40 W.

[0060] (2) Deposition: After cleaning, turn off the argon gas and RF power supply. The seven independent mass flow meters are set as follows:

[0061] First route: CHF3, flow rate 4 sccm;

[0062] Second route: O2, flow rate 4 sccm;

[0063] Third path: N2, flow rate 7 sccm;

[0064] The fourth route: TiCl4 liquid vapor at 20°C is carried by 2 sccm of argon gas; the amount of vapor carried is the amount that reaches its saturated vapor pressure under the carrying temperature and atmospheric pressure conditions, and the specific amount carried is already implied in the above description.

[0065] Fifth route: SF6, flow rate 2 sccm;

[0066] The sixth route: BBr3 liquid vapor at 15°C is carried by 5 sccm of argon gas; the amount of vapor carried is the amount that reaches its saturated vapor pressure under the carrying temperature and atmospheric pressure conditions, and the specific amount carried is already implied in the above description.

[0067] Channel 7: HI gas, flow rate 4 sccm.

[0068] The gas pipeline was insulated at 40℃. The throttle valve was adjusted to achieve a steady-state pressure of 5 Pa in the chamber. The ICP RF power supply was turned on at a frequency of 13.56 MHz (hereinafter the same) and a power of 100 W. The substrate temperature was maintained at 20±2℃ using water cooling. Continuous deposition was performed for 5 minutes.

[0069] (3) Annealing: Turn off all gas sources and radio frequency power supply, maintain vacuum, heat to 40°C and hold for 5 minutes, cool naturally to 28°C and take out to obtain film composite anode material.

[0070] Product characterization methods: The molar ratio of lithium ions to each anion in the high-entropy SEI film was determined using the same X-ray photoelectron spectroscopy (XPS, optional Ar) method. + Characterization using deep etching yielded the following results: a single sample full spectrum and narrow spectrum of each element were acquired. Li 1s spectrum peaking was used to screen for combined lithium ion signals, and narrow spectrum peaking for each of F, O, N, Cl, S, Br, and I elements was used to screen for target anion characteristic signals. After sensitivity factor correction and removal of impurity peaks, all values ​​were converted to ion mole fractions. Product characterization was performed in the same manner in the following examples.

[0071] The results showed that the molar fraction of lithium ions in the high-entropy SEI film was 55%, with the remaining molar fraction consisting of seven anions. The total amount of the seven anions was 100 mol%, and the molar fraction of each anion was: F - 20%, O 2- 25%, N 3- 25%, Cl - 5%, S 2- 5%, Br - 10%, I - 10%. Cross-sectional SEM film thickness: 70 nm. X-ray diffraction (XRD) shows it to be amorphous. Ionic conductivity: 1.5 × 10⁻⁶. -5 S / cm.

[0072] Electrochemical test: Symmetric cell 1 mA / cm 2 1 mAh / cm 2 After 1000 hours of cycling, the overpotential was 32±4mV, and no short circuit was observed. The critical current density was 3.3 mA / cm². 2 .

[0073] Figure 1 and Figure 2 The images show the cross-sectional SEM and X-ray diffraction (XRD) patterns of the high-entropy SEI film in Example 1. As can be seen from the two images, a high-entropy SEI film with a uniform and dense surface and a completely amorphous structure was successfully prepared using this multi-gas-source ICP-PECVD process. This structural feature matches the core requirements of lithium metal anodes for SEI films, providing structural assurance for suppressing lithium dendrite growth and improving cycle stability.

[0074] Example 2

[0075] Preparation steps of composite anode materials:

[0076] (1) Pretreatment: Base vacuum 5×10 -4 Pa, introduce 30 sccm of high-purity argon gas, chamber pressure 15 Pa, RF power 80 W, clean for 3 minutes.

[0077] (2) Deposition: The seven gas channels are set up as follows:

[0078] First channel: CHF3, flow rate 12 sccm;

[0079] Second route: O2, flow rate 1 sccm;

[0080] Third path: N2, flow rate 2 sccm;

[0081] Fourth route: TiCl4 liquid vapor at 30℃ is carried by 6 sccm of argon gas;

[0082] Fifth route: SF6, flow rate 6 sccm;

[0083] Sixth route: BBr3 liquid vapor at 25℃ is carried by 2 sccm of argon gas;

[0084] Channel 7: HI gas, flow rate 1 sccm.

[0085] The gas pipeline was insulated at 60℃. The steady-state pressure in the chamber was 30 Pa. The ICP power was 300 W, and the substrate temperature was 35±2℃. Continuous deposition lasted for 60 minutes.

[0086] (3) Annealing: Maintain vacuum, heat to 80°C and hold for 30 minutes, cool naturally and remove to obtain film-like composite anode material.

[0087] Product characterization results showed that the molar fraction of lithium ions in the high-entropy SEI film was 70%, with the remaining molar fraction consisting of seven anions. The total amount of the seven anions was 100 mol%, and the molar fraction of each anion was: F - 40%, O 2- 10%, N 3- 10%, Cl - 15%, S 2- 15%, Br - 5%, I - 5%. Film thickness 480 nm, amorphous. Ionic conductivity 6.5 × 10⁻⁶. -6 S / cm.

[0088] Electrochemical testing: Symmetrical cell cycled at 1 mA / cm² and 1 mAh / cm² for 1000 hours, overpotential 45±5 mV, no short circuit. Critical current density 3.0 mA / cm².

[0089] Figure 3 and Figure 4 The images show the cross-sectional SEM and X-ray diffraction (XRD) patterns of the high-entropy SEI film in Example 2. As can be seen from the two images, by adjusting the ICP-PECVD process parameters (increasing deposition power, chamber pressure, and deposition time), a continuous, dense, completely amorphous high-entropy SEI film with higher surface roughness was successfully prepared. This structural characteristic ensures that it still possesses good long-term cycling stability, but its ion transport performance is slightly lower than that of Example 1, demonstrating the regulatory effect of process parameters on the morphology, structure, and properties of the SEI film.

[0090] Example 3

[0091] Preparation steps of composite anode materials:

[0092] (1) Pretreatment: Base vacuum 4.5×10 -4 Pa, argon flow rate 22 sccm, chamber pressure 12 Pa, radio frequency power 60 W, cleaning for 6 minutes.

[0093] (2) Deposition: The seven gas channels are set up as follows:

[0094] First channel: CHF3, flow rate 8 sccm;

[0095] Second route: O2, flow rate 1.5 sccm;

[0096] Third channel: N2, flow rate 2.5 sccm;

[0097] Fourth route: TiCl4 liquid vapor at 25℃ is carried by 4 sccm of argon gas;

[0098] Fifth route: SF6, flow rate 5 sccm;

[0099] Sixth route: BBr3 liquid vapor at 20℃ is carried by 2 sccm of argon gas;

[0100] Channel 7: HI gas, flow rate 1 sccm.

[0101] The gas pipeline was insulated at 50℃. The total gas flow rate was approximately 24 sccm, and the steady-state pressure in the chamber was 15 Pa. The ICP power was 200 W, and the substrate temperature was 28±2℃. Continuous deposition lasted for 30 minutes.

[0102] (3) Annealing: Heat to 60℃ and hold for 18 minutes, then cool naturally and remove to obtain a film-like composite negative electrode material.

[0103] Product characterization results showed that the molar fraction of lithium ions in the high-entropy SEI film was 60%, with the remaining molar fraction consisting of seven anions. The total amount of the seven anions was 100 mol%, and the molar fraction of each anion was: F- 32%, O 2- 18%, N 3- 18%, Cl - 13%, S 2- 13%, Br - 3%, I - 3%. Film thickness 250 nm, amorphous. Ionic conductivity 9.0 × 10⁻⁶. -6 S / cm.

[0104] Electrochemical test: Symmetric cell 1 mA / cm 2 1 mAh / cm 2 After 1050 hours of cycling, the overpotential was 39±5 mV, and no short circuit was observed. The critical current density was 3.1 mA / cm². 2 .

[0105] Example 4

[0106] Preparation steps of composite anode materials:

[0107] (1) Pretreatment: Base vacuum 5×10 -4 Pa, argon flow rate 18 sccm, chamber pressure 10 Pa, radio frequency power 50 W, cleaning for 8 minutes.

[0108] (2) Deposition: The seven gas channels are set up as follows:

[0109] First channel: CHF3, flow rate 8 sccm;

[0110] Second route: O2, flow rate 3 sccm;

[0111] Third channel: N2, flow rate 4.5 sccm;

[0112] Fourth route: TiCl4 liquid vapor at 22℃ is carried by 2.5 sccm of argon gas;

[0113] Fifth route: SF6, flow rate 2 sccm;

[0114] Sixth route: BBr3 liquid vapor at 18℃ carried by 5 sccm of argon gas;

[0115] Channel 7: HI gas, flow rate 2.5 sccm.

[0116] Gas path insulation at 55℃. Chamber steady-state pressure 25 Pa. ICP power 280 W, substrate temperature 23±2℃. Continuous deposition for 50 minutes.

[0117] (3) Annealing: Heat to 50°C and hold for 25 minutes, then cool naturally and remove to obtain a film-like composite anode material.

[0118] Product characterization results showed that the molar fraction of lithium ions in the high-entropy SEI film was 58%, with the remaining molar fraction consisting of seven anions. The total amount of the seven anions was 100 mol%, and the molar fraction of each anion was: F - 30%, O 2- 18%, N 3- 18%, Cl - 7%, S 2- 7%, Br - 10%, I - 10%. Film thickness 400 nm, amorphous. Ionic conductivity 1.6 × 10⁻⁶ -5 S / cm.

[0119] Electrochemical test: Symmetric cell 1 mA / cm 2 1 mAh / cm 2 After 1150 hours of cycling, the overpotential was 30 ± 4 mV, and no short circuit was observed. The critical current density was 3.5 mA / cm². 2 .

[0120] Example 5

[0121] Preparation steps of composite anode materials:

[0122] (1) Pretreatment: Base vacuum 4.5×10 -4 Pa, argon flow rate 22 sccm, chamber pressure 12 Pa, radio frequency power 60 W, cleaning for 6 minutes.

[0123] (2) Deposition: The seven gas channels are set up as follows:

[0124] First channel: CHF3, flow rate 8 sccm;

[0125] Second route: O2, flow rate 3 sccm;

[0126] Third channel: N2, flow rate 4.5 sccm;

[0127] Fourth route: TiCl4 liquid vapor at 25℃ is carried by 4 sccm of argon gas;

[0128] Fifth channel: SF6, flow rate 4 sccm;

[0129] Sixth route: BBr3 liquid vapor at 20℃ is carried by 3.5 sccm of argon gas;

[0130] Channel 7: HI gas, flow rate 2.5 sccm.

[0131] The gas pipeline was insulated at 50℃. The steady-state pressure in the chamber was 17 Pa. The ICP power was 200 W, and the substrate temperature was 28±2℃. Continuous deposition lasted for 33 minutes.

[0132] (3) Annealing: Heat to 60℃ and hold for 18 minutes, then cool naturally and remove to obtain a film-like composite negative electrode material.

[0133] Product characterization results showed that the molar fraction of lithium ions in the high-entropy SEI film was 62%, with the remaining molar fraction consisting of seven anions. The total amount of the seven anions was 100 mol%, and the molar fraction of each anion was: F - 30%, O 2- 18%, N 3- 18%, Cl - 10%, S 2- 10%, Br - 7%, I - 7%. Film thickness 275 nm, amorphous. Ionic conductivity 1.5 × 10⁻⁶. -5 S / cm.

[0134] Electrochemical test: Symmetric cell 1 mA / cm 2 1 mAh / cm 2 After 1300 hours of cycling, the overpotential was 33±5 mV, and no short circuit was observed. The critical current density was 3.5 mA / cm². 2 .

[0135] Comparative Example 1 (Pure LiF single-component SEI)

[0136] The preparation steps were basically the same as in Example 5, except that only CHF3 was introduced as the sole precursor during deposition at a flow rate of 8 sccm, without introducing other precursor gases; all other parameters remained the same. The resulting film was pure LiF. - Atomic percentage 100%, Li content 50%, thickness 270 nm. XRD shows polycrystalline state. Room temperature ionic conductivity 4.2 × 10⁻⁶. -9 S / cm. Symmetrical cells at 0.5 mA / cm 2 0.5 mAh / cm 2 Under cyclic conditions, the initial overpotential was 180 mV, and after 45 hours the overpotential dropped sharply to below 10 mV, and lithium dendrites pierced the film.

[0137] Comparative Example 2 (Naturally Oxidized SEI Film)

[0138] A fresh lithium foil with a thickness of 50 μm was placed directly in a glove box containing approximately 1 ppm O2 and 0.5 ppm H2O and left to stand for 24 hours, resulting in the natural formation of a selenium ionization (SEI) on the surface. XPS analysis showed that the main components were Li2O and LiOH, with uneven thickness ranging from approximately 50 to 80 nm and a porous surface. A symmetric cell was generated at 0.2 mA / cm². 20.2 mAh / cm 2 In the next cycle, the overpotential exceeded 200 mV in the first cycle, and a short circuit occurred in the 8th cycle.

[0139] Comparative Example 3 (Ternary SEI membrane, containing only F) - O 2- N 3- )

[0140] During deposition, only three precursor pathways—CHF3 (8 sccm), O2 (3 sccm), and N2 (4.5 sccm)—were introduced, while the other four pathways were shut off. All other parameters were the same as in Example 5. The resulting film composition was F. - 52%, O 2- 28%, N 3- 20% Li content, 58% Li content, thickness 260 nm. XRD shows weak broadening peaks, indicating microcrystalline LiF precipitation. Ionic conductivity 2.0 × 10⁻⁶ -7 S / cm. Symmetrical cell 1 mA / cm 2 1 mAh / cm 2 Cyclic operation, initial overpotential 85 mV, short circuit after 380 hours, critical current density only 1.1 mA / cm² 2 .

[0141] As can be seen from the test data of various embodiments and comparative examples, the single-phase amorphous high-entropy SEI film containing seven anions prepared in this invention has an ionic conductivity of 10. -6 Up to 10 -5 The S / cm ratio is on the order of magnitude, which is 3 to 4 orders of magnitude higher than that of pure LiF films, and significantly better than SEI films containing only three anions. In symmetric cell tests, the composite anode using this high-entropy SEI film exhibits excellent cycle stability (over 1000 hours) and a high critical current density (3.0 mA / cm). 2 The above measures effectively suppressed the growth of lithium dendrites. This fully demonstrates the synergistic effect of the high-entropy design with multiple anion species in broadening ion transport channels, enhancing the stability of amorphous structures, and dispersing local stress, achieving a comprehensive improvement in high ionic conductivity, high interface stability, and excellent mechanical properties.

[0142] The specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the specific embodiments described above, and those skilled in the art can make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A lithium metal-high-entropy solid electrolyte interface film composite anode material, characterized in that, This includes a lithium metal substrate and a high-entropy solid electrolyte interface film grown in situ on the substrate surface, the latter containing F - O 2- N 3- Cl - S 2- ,Br - I - These are single-phase amorphous lithium-containing inorganic compound films containing seven anions.

2. The composite negative electrode material according to claim 1, characterized in that, In the high-entropy solid electrolyte interface membrane, the molar fraction of lithium ions in the high-entropy SEI membrane is 55%~70%, and the remaining molar percentage is composed of the seven types of anions.

3. The composite negative electrode material according to claim 1, characterized in that, The total amount of the seven anions is 100 mol%, and the mole fraction of each anion is: F - 20%–40%, O 2- 10%–25%, N 3- 10%–25%, Cl - 5%–15%, S 2- 5%–15%, Br - 3% to 10%, I - It ranges from 3% to 10%.

4. The composite negative electrode material according to claim 1, characterized in that, The thickness of the high-entropy solid electrolyte interface film is 70~480 nanometers.

5. The method for preparing the lithium metal-high entropy solid electrolyte interface film composite anode material according to any one of claims 1 to 4, characterized in that, Includes the following steps: (1) The lithium metal used as the negative electrode substrate is shaped and cleaned; (2) In an inductively coupled plasma enhanced chemical vapor deposition system, a precursor gas containing different anions is introduced simultaneously; a single-phase amorphous lithium-containing inorganic compound film containing seven anions is deposited in situ on the surface of a lithium metal substrate by plasma in situ deposition. (3) After heating and heat preservation treatment of the material deposited on the surface, it is annealed in situ by natural cooling to obtain the metal lithium-high entropy solid electrolyte interface film composite negative electrode material.

6. The method according to claim 5, characterized in that, The shaping in step (1) refers to cutting and flattening the lithium metal foil in an inert atmosphere or vacuum environment; the cleaning process refers to placing the lithium metal foil in the deposition chamber, evacuating it, and then introducing argon gas to bombard its surface with radio frequency plasma to remove the natural oxide layer and adsorbed impurities.

7. The method according to claim 5, characterized in that, The precursor gas in step (2) refers to the precursor gas containing different anions; among them, the fluorine source is CHF3, the oxygen source is O2, the nitrogen source is N2, the chlorine source is TiCl4 vapor, the sulfur source is SF6, the bromine source is BBr3 vapor, and the iodine source is HI gas; both TiCl4 vapor and BBr3 vapor are introduced into the deposition system by bubbling with argon as the carrier gas.

8. The method according to claim 5, characterized in that, In step (2), the flow rate of each gas, the total pressure of the chamber, the plasma radio frequency power, and the deposition time are adjusted. Each precursor gas is precisely controlled by an independent mass flow meter, and all gas pipelines are heated and kept at 40~60℃. The steady-state pressure of the deposition chamber is maintained at 5~30 Pa. The plasma radio frequency power supply frequency is 13.56 MHz and the power is 100~300 W. The deposition time is 5~60 minutes.

9. The method according to claim 5, characterized in that, In step (2), the temperature of the sample stage supporting the lithium metal substrate is controlled by a circulating constant temperature water cooling system during the deposition process, and the temperature is maintained at 20~35℃.

10. The method according to claim 5, characterized in that, In step (3), after deposition, the sample stage is heated to 40-80°C using the heating resistance wire inside. After holding the temperature for 5-30 minutes, it is naturally cooled to below 30°C. The residual stress in the film is released and the amorphous structure is stabilized by in-situ annealing.